Comics as a transmitter of an ideological conflict: the case of Wonder Woman and The Sovereign - Llanos Illescas, Luis Fernando (2025)
Liberalism has always had its proponents, not only in the realm of ideological thought but also in popular culture. One of its most recognized representatives worldwide is Wonder Woman. This comic book character has always represented classic liberal values, such as the development of a personal life plan without the necessary intervention of a third party. In this episode, we’llanalyze the comics written by Tom King from the Dawn of DC series. In it, we’ll address the conflict between the superheroine and the well-known villain The Sovereign, a figure who champions conservative ideas. In this sense, we can see how the conflict between these two fictional characters reflects the current ideological struggle that exists in contemporary politics betweenliberals and conservatives.